Educate Based on Vedic Teachings: Guru Bhakti and Guru Susrusa in The Story of Bhagawan Dhomya - Adnyana, Putu Eka Sura; Arta, Putu Eddy Purnomo (International Journal of Multidisciplinary Sciences, 2025)
The story of Bhagawan Dhomya indicates that an Old Javanese narrator was able to integrate the education system and educate based on the Vedic teachings illustrated in the storyline. Bhagawan Dhomya is considered a teacher and 'god of sekala' (agent of change) who has credibility and authority in educating his three students. Data analysis by reviewing all research data obtained through observation, recording, documents, and so on. The results of this research will be presented using informal methods. Bhagavan Dhomya gave a test instruction to find out the constancy of the three students. teaching carried out by the teacher from students listening to what is conveyed by the teacher with full attention. Bhagavan Dhomya as a teacher is highly respected and obeyed by his three students. The guru in the Vedic tradition is someone who should be honored or guided. The guru in the Vedic view is someone who has high qualities in various aspects. The work of Bhagavan Dhomya's inspirational story to students can reflect their character so that they will care about social, obedient, devoted and obedient to the teacher in gaining knowledge.